Insulin Analogs - Buckley, Rita (MD Conference Express, 2012)
The basal insulin analog LY2605541 (LY) is a long-acting, PEGylated insulin lispro that is designed with a large hydrodynamic size, which delays insulin absorption and reduces clearance, resulting in prolonged duration of action. LY demonstrates a preferential hepatic effect compared with human insulin in a somatostatin-infused/glucagon-replaced conscious dog model [Moore MC et al. ADA 2012 Abstract 1609P]. This article discusses data that showed that in a continuously glucose-monitored cohort of patients with type 2 diabetes mellitus, those receiving LY had lower intra-day glucose variability and fewer and shorter episodes of hypoglycemia compared with patients receiving glargine.